PENGARUH PENDIDIKAN KESEHATAN TENTANG DETEKSI DINI GANGGUAN JIWA PADA PENGETAHUAN DAN SIKAP KADER - Pratama, Fajar Angga Setia, Arif Widodo., A.Kep., M.Kep (2016)
Early detection is a preventive measure against the recurrence prevention of mental disorders . In this detection needs the participation of the entire community, one cadre of health. The aim of this research is knowing effect of health education on knowledge and attitude of health cadre about early detection of relapse of sychiatric disorder in the Makam haji village districts Kartasura. Method of research use a pre-experimental design of One-Group Pre-Test-Posttest Design. The samples is all of health cadre. Taking sample is using Total Sampling technique. Research instrument from knowledge and attitude questionnaires given at pre-test and post test. Data analysis is using Paired t-Test. The results of research that Pre testof knowledge has average score = 10,43 point and post-test = 15,43 point. Results of Paired t-test knowladge obtained t-test = 10,226, p = 0.000. pre-test attitude has average scocer = 56,07 point and post-test = 60,93 point. Paired t-test attitude results obtained t-tst = 9,016, p = 0.000. The conclusion was that there are significant changes in the level of health education on knowledge and attitude of health cadre about early etection of relapse of psychiatric disorder in the Makam haji village districts Kartasura.